Evaluation of parameters affecting gamma passing rate in patient‐specific QAs for multiple brain lesions IMRS treatments using ray‐station treatment planning system. Issue 1 (18th November 2021) - Salari, Elahheh; Parsai, E. Ishmael; Shvydka, Diana; Sperling, Nicholas Niven
Abstract: Purpose: Using intensity‐modulated radiosurgery (IMRS) with single isocenter for the treatment of multiple brain lesions has gained acceptance in recent years. One of the challenges of this technique is conducting a patient‐specific quality assurance (QA), involving accurate gamma passing rate (GPR) calculations for small and wide spread‐out targets. We evaluated effects of parameters such as dose grid and energy on GPR using our clinical IMRS plans. Methods: Ten patients with total of 40 volumetric modulated arc therapy (VMAT) plans were created in Raystation (V.8A) treatment planning system (TPS) for the Varian Edge Linac using 6 and 10 flattening filter‐free (FFF) beams and planned dose grids of 1 mm and 2 mm resulting in four plans with 6–10 targets per patient. All parameters and objectives except dose grid and energy were kept the same in all plans. Next, patient‐specific QAs were measured evaluating GPR with 10% threshold, 3%/3 mm objective, and an acceptance criterion of 95%. Modulation factors (MF) and confidence intervals were calculated. Two modes of measurements, standard density (SD) and high density (HD), were used. Results: Generally, plans computed with 1 mm dose grid have higher GPRs than those with 2 mm dose grid for both energies used. The GPRs of 6 FFF plans were higher than those of 10 FFF plans. GPR showed no noticeable difference between HD and SD measurements. Negative correlation between MF and GPR was observed. The HD pass rates fall within the confidence interval of SD. Conclusion: Calculated dose grid should be less than or equal to one‐third of distance to agreement, thus 1 mm planned dose grid is recommended to reduce artifacts in gamma calculation. GPR of SD and HD measurement modes is almost the same, which indicates that SD mode is clinically preferable for performing patient‐specific QAs. According to our results, using 6 FFF beams with 1 mm planned dose grid is more accurate and reliable for dose calculation of IMRS plans.